2021
DOI: 10.1039/d0sm01399d
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanically active electrodes power work-dense soft actuators

Abstract: The effect of chain extender structure and composition on the properties of liquid crystal elastomers (LCE) is presented. Compositions are optimized to design work-dense liquid metal LCE composites that are operated with 100 mW power.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
0
9
2
Order By: Relevance
“…[ 14 ] Mixtures were harnessed containing a 1:1.2 mole ratio of RM82: EDDT were used to create monodomain LCE using the procedure utilized in the prior work. [ 13 ] The procedure is detailed in the Supporting Information, along with the structure of the monomers (Figure S1, Supporting Information) and the polarized optical microscopy images of the crosslinked films (Figure S2, Supporting Information). Dynamic mechanical analysis was performed using a Perkin Elmer 8000 system with the loading applied along the molecular director.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 14 ] Mixtures were harnessed containing a 1:1.2 mole ratio of RM82: EDDT were used to create monodomain LCE using the procedure utilized in the prior work. [ 13 ] The procedure is detailed in the Supporting Information, along with the structure of the monomers (Figure S1, Supporting Information) and the polarized optical microscopy images of the crosslinked films (Figure S2, Supporting Information). Dynamic mechanical analysis was performed using a Perkin Elmer 8000 system with the loading applied along the molecular director.…”
Section: Methodsmentioning
confidence: 99%
“…The lengths were measured along the director. The inflection point of the strain-temperature curve, where the strain production per temperature increase is the highest was characterized (the nominal T ni : nematic-isotropic transition [13,21] ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 205 ] In addition to carbon‐based additives, LM–LCE composites have also been explored, taking advantage of the compliancy of LM to achieve a conductive, mechanically unconstrained LCE. [ 210–212 ] Ford et al demonstrated that even with a significantly high LM wt loading of 50% in an LCE, its actuation capabilities were still retained (Figure 8C). [ 210 ] These composites possessed damage detection capabilities and were able to actuate despite sustaining significant punctures.…”
Section: Materials Developments For the Active Layermentioning
confidence: 99%
“…There are two basic criteria for elastomers with supreme mechanical adaptability, namely, the sufficiently high tensile strength at the onset of stress plateau and the length of the stress plateau. Most research on liquid crystal elastomers focuses on developing environmental response materials, such as temperature, light, and magnetic responsiveness [28][29][30][31]. And the mechanical tensile strength in previous literatures almost never exceeds 1 MPa [7,17,19,30,31].…”
Section: Introductionmentioning
confidence: 99%